The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2023
DOI: 10.3390/ijms24065606
|View full text |Cite
|
Sign up to set email alerts
|

Influence of HA on Release Process of Anionic and Cationic API Incorporated into Hydrophilic Gel

Abstract: The properties of sodium hyaluronate (HA), such as hygroscopicity, flexibility, the ability to form hydrogels, as well as biocompatibility and biodegradability, are beneficial for the applications in pharmaceutical technology, cosmetics industry, and aesthetic medicine. The aim of this study was to prepare HA-based hydrogels doped with active pharmaceutical ingredient (API): a cationic drug—lidocaine hydrochloride or anionic drug—sodium. The interaction between the carrier and the implemented active pharmaceut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
14
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(19 citation statements)
references
References 57 publications
5
14
0
Order By: Relevance
“…Notably, the HA-HS conditions exhibited higher moisture retention percentages compared to HA-DI across all HA concentration ranges from 0.5% to 3%. The hygroscopic properties of HA [37] enable it to attract and retain water molecules from the surrounding environment effectively, thus hydrating the skin by drawing moisture from the air and deeper layers of the skin. Additionally, HA plays a role in supporting the skin's natural barrier function by maintaining adequate moisture levels in the outermost layer of the skin [38].…”
Section: Incorporation Of Hs Water In Combination With Ha As a Moistu...mentioning
confidence: 99%
“…Notably, the HA-HS conditions exhibited higher moisture retention percentages compared to HA-DI across all HA concentration ranges from 0.5% to 3%. The hygroscopic properties of HA [37] enable it to attract and retain water molecules from the surrounding environment effectively, thus hydrating the skin by drawing moisture from the air and deeper layers of the skin. Additionally, HA plays a role in supporting the skin's natural barrier function by maintaining adequate moisture levels in the outermost layer of the skin [38].…”
Section: Incorporation Of Hs Water In Combination With Ha As a Moistu...mentioning
confidence: 99%
“…The kinetic analysis was carried out using zero-, first-, and second-order kinetics as well as Higuchi and Korsmeyer-Peppas dependences [31][32][33][34]. The equations were included in our previous work [23,35,36], and they are as follows:…”
Section: Kinetic Studymentioning
confidence: 99%
“…The measured viscosity of the formulations F1-F3 containing Nap and Lid, in comparison to the viscosity of the corresponding Lid-free hydrogels assessed in previous work [23], is listed in Table 2. It was found that the viscosity of the preparations F1-F3 was lower than the corresponding viscosity of hydrogels with Nap only.…”
Section: Viscosity Studymentioning
confidence: 99%
See 2 more Smart Citations